CLINICAL EXPERIENCE AND FEATURES OF THE BRAIN PERFUSION MSCT TECHNIQUE FOR SURGICAL CORRECTION OF COMBINED LESIONS OF THE CORONARY AND CAROTID ARTERIES (World Bulletin of Public Health, 2024)
This study addresses the critical issue of optimizing surgical strategies for patients with combined coronary and carotid artery lesions through advanced brain perfusion imaging. The aim was to evaluate the clinical utility and technical aspects of brain perfusion MSCT in preoperative planning and postoperative monitoring of patients undergoing combined surgical correction. The study included patients (n=124) with concurrent coronary and carotid artery disease who underwent brain perfusion MSCT before and after surgical intervention. The perfusion protocol was optimized to minimize radiation exposure while maintaining diagnostic accuracy. Key parameters analyzed included cerebral blood flow (CBF), cerebral blood volume (CBV), and mean transit time (MTT). Results demonstrated that brain perfusion MSCT effectively identified perfusion deficits in 78% of cases, influencing surgical strategy in 45% of patients. Post-surgical imaging showed significant improvement in perfusion parameters in 82% of cases. Technical refinements in the MSCT protocol resulted in a 30% reduction in radiation dose without compromising diagnostic quality. This experience suggests that brain perfusion MSCT is an essential tool for surgical planning and outcome assessment in combined coronary-carotid interventions, providing valuable hemodynamic information for optimizing treatment strategies.
Keywords: brain perfusion MSCT; coronary artery disease; carotid artery stenosis; surgical correctio